Alanine-mediated P cycle boosting enhances the killing efficiency of kasugamycin on antibiotic-resistant Xanthomonas oryzae - Guan, Yi; Lin, Meiyun; Shen, Peihua; Zou, Zhenyu (Frontiers in Microbiology, 2023)
The outbreak of Bacterial blight (BB) caused by Xanthomonas oryzae (Xoo) generates substantial economic losses to agricultural production. Antibiotics application is a valuable measure to control this bacterial disease. However, microbial antibiotic resistance dramatically reduced antibiotic effectiveness. Identifying the resistance mechanism of Xoo to antibiotics and restoring antibiotic susceptibility is one of the crucial ways to solve this problem. This study employed a GC-MS-based metabolomic approach to reveal the differential metabolomics between a kasugamycin-susceptible Xoo strain (Z173-S) and a kasugamycin-resistant strain (Z173-RKA). The results showed that the downregulation of the pyruvate cycle (P cycle) is a crucial feature of Z173-RKA resistance to kasugamycin (KA). This conclusion was confirmed by the decreased enzyme activities and the related gene transcriptional level in the P cycle. Furfural (an inhibitor of pyruvate dehydrogenase) can effectively inhibit the P cycle and increase the resistance of Z173-RKA to KA. Moreover, exogenous alanine can reduce the resistance of Z173-RKA to KA by promoting the P cycle. Our work seems to be the first exploration of the mechanism of KA resistance in Xoo by GC-MS-based metabonomics approach. These results provide a new idea for developing metabolic regulation to address KA resistance in Xoo.